South Atlantic subtropical anticyclone responses to stratospheric aerosol injection - Thales Chile Baldoni; Michelle Simões Reboita; Natália Machado Crespo; João Gabriel Martins Ribeiro; Rosmeri Porfírio da Rocha (Environmental Research: Climate)
The South Atlantic Subtropical Anticyclone (SASA) is a key component of large-scale atmospheric circulation and is responsible for driving the climate in eastern Brazil and western Africa. Climate projections under warming scenarios suggest a strengthening, as well as a westward and southward expansion of this system. However, little is known about how the combination of global warming and climate intervention affects this system. To address this, SASA was identified from 2015 to 2099 in a set of projections with and without stratospheric aerosol injection (SAI). Projections were obtained from different initiatives: the Assessing Responses and Impacts of Solar Climate Intervention on the Earth System with SAI using Community Earth System Model version 2 (CESM2) global climate model, the Stratospheric Aerosol Geoengineering Large Ensemble (GLENS) using CESM1, and the Geoengineering Model Intercomparison Project (GeoMIP/G6sulfur) using Max Planck Institute Earth System Model. As each project has its own specific model, scenario, SAI location, etc, no intercomparison was carried out among them. Instead, there is an indication of what occurs in each project when comparing the near (2040–2059) and the far future (2080–2099) projections under SAI and no-SAI scenarios. SASA under no-SAI scenarios, compared to the reference period (2015–2024), follows the pattern described in the literature, i.e. a tendency to be stronger and wider. However, these features are more evident in the GLENS project. This same project suggests that SAI scenarios contribute to reducing the impact of global warming on the SASA climatology, as SASA in the future acquires characteristics similar to those of the reference period. One of the possibilities for it is that GLENS has the largest SAI forcing, given that the goal was to cancel out the strong greenhouse gas-induced warming in Representative Concentration Pathway 8.5.